TINJAUAN FIKIH MUAMALAH TERHADAP PRODUK MITRAGUNA BERKAH DALAM PEMBIAYAAN MULTIGUNA MENGGUNAKAN AKAD MURABAHAH BIL WAKALAH PADA BANK SYARIAH INDONESIA - NIM. A1011211269, RIZKI AMALIA (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract The development of contract in the form of multiple contracts as a form of creativity and innovation by Sharia Financial Institutions in developing their products. The combination of two or more contracts in a single agreement or transaction is commonly practices in Sharia Financial Institutions, for example, the Murabahah Bil Wakalah contract, which is a sale and purchase contract involving representation in the purchase of goods. The issues related to the implementation ad fiqh muamalah review of the Mitraguna Berkah product using the Murabahah Bil Wakalah contract. The methods used in this research is the normative juridical method with an approach that examines theories, concepts, ad reviews related laws and regulations. This research examines Mitraguna Berkah products that use Murabahah Bil Wakalah contracts in accordance with fikih muamalah, Qur